2022
DOI: 10.3390/pharmaceutics14061289
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Analysis of Voriconazole Treatment in Children

Abstract: Voriconazole is among the first-line antifungal drugs to treat invasive fungal infections in children and known for its pronounced inter- and intraindividual pharmacokinetic variability. Polymorphisms in genes involved in the metabolism and transport of voriconazole are thought to influence serum concentrations and eventually the therapeutic outcome. To investigate the impact of these genetic variants and other covariates on voriconazole trough concentrations, we performed a retrospective data analysis, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“… Chen et al [ 29 ] Retrospective, single-center study 0.5 months to 17 36 2022 Switzerland CYP2C19 and CYP3A4 polymorphisms and drug transporters ABCC2 and ABCG2, combination medication levetiracetam, ciprofloxacin, and propranolol affected VRC C trough . Tilen et al [ 30 ] Prospectively single-center study 2 to 14 68 2022 China VRC C trough of patients with CYP2C19*2 or CYP2C19*3 were significantly higher than that with wild-type carriers. Fan et al [ 31 ] Retrospective, single-center study 2 to 14 131 2023 China CYP2C19 polymorphisms, co-administration of omeprazole, ALB and ALT levels affected VRC C trough .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Chen et al [ 29 ] Retrospective, single-center study 0.5 months to 17 36 2022 Switzerland CYP2C19 and CYP3A4 polymorphisms and drug transporters ABCC2 and ABCG2, combination medication levetiracetam, ciprofloxacin, and propranolol affected VRC C trough . Tilen et al [ 30 ] Prospectively single-center study 2 to 14 68 2022 China VRC C trough of patients with CYP2C19*2 or CYP2C19*3 were significantly higher than that with wild-type carriers. Fan et al [ 31 ] Retrospective, single-center study 2 to 14 131 2023 China CYP2C19 polymorphisms, co-administration of omeprazole, ALB and ALT levels affected VRC C trough .…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al‘s study [ 29 ] found that 15.3% of patients were CYP2C19 poor metabolizers (PMs), a proportion higher than that reported in European and American populations. Allegra et al [ 23 ] and Tilen et al [ 30 ] reported that apart from CYP2C19 genotypes, genetic polymorphisms in CYP3A4, SLCO1B3, as well as ABCC2 and ABCG2 also significantly influenced VRC C trough .…”
Section: Resultsmentioning
confidence: 99%
“…In a larger study of 233 pediatric patients receiving voriconazole treatment, SNPs in SLCO1B3, ABCG2, and ABCB1 were signi cantly associated with trough concentrations (19). A study of 36 pediatric patients receiving voriconazole treatment demonstrated that CYP2C19, CYP3A4, ABCC2, and ABCG2 were associated with voriconazole concentrations (20). However, the minor allele frequency for CYP3A4 was 5%, and the study sample size was small.…”
Section: Discussionmentioning
confidence: 96%
“…Overall, the VRZ daily dose was positively correlated with its trough concentration significantly, which demonstrates that the necessity of reducing the VRZ dose in patients with liver dysfunction. Besides, some other factors that contribute to unpredictability of VRZ trough concentrations have been reported in published literature, such as inflammation ( van Wanrooy et al, 2014 ; Encalada Ventura et al, 2016 ), polymorphism within drug transporters ( Tilen et al, 2022 ), and the use of extracorporeal membrane oxygenation ( Ye et al, 2022 ). In the analysis of relationship between CYP2C19 and initial VRZ trough concentration, our results were similar to previously studies ( Kim et al, 2019 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%